NLRP3 neuroinflammatory factors may be involved in atopic dermatitis mental disorders: an animal study - Yuan, Huimin; Sun, Yan; Zhang, Shujing; Feng, Jing; Tian, Zijiao; Liu, Jingang; Wang, Hang; Gao, Yushan; Tang, Yang; Zheng, Fengjie (Frontiers in Pharmacology, 2022)
Abstract Background: Numerous clinical studies have shown that atopic dermatitis (AD) is often associated with mental disorders. This could contribute to the overall burden of atopic dermatitis. However, the underlying mechanism of mental health symptoms in AD has not been fully elucidated. Methods: The AD mouse was induced by 2,4-dinitrofluorobenzene (DNFB), which was repeatedly applied to the back skin of BALB/C mice to establish an atopic dermatitis mental disorder model. The role of neuroinflammation in the pathogenesis of atopic dermatitis mental disorder was then explored. Results: After the stimulation of DNFB for 35 days, the skin lesions, the HE staining of skin lesions, and the behavioral experiments (including elevated plus maze assay and tail suspension test) suggested the AD mental disorder mouse model was successfully replicated. The expression of neuroinflammatory factors in the hippocampus was then investigated through Western Blotting. Results showed a significant increase in protein expression of NLRP3, Caspase-1, and IL-1β. Conclusion: Mental disorders in AD might be related to the neuroinflammatory response in the hippocampus. An alternative yet essential approach to promoting AD recovery could be through reducing neuroinflammation and improving mental disorders.